Redescription of the subgenus Securiops Jacobus, McCafferty & Gattolliat 2006 (Ephemeroptera, Baetidae, Procloeon Bengtsson 1915) - Kluge, Nikita J. (Zootaxa, 2023)
The taxon Securiops Jacobus, McCafferty & Gattolliat 2006 is treated here as a subgenus of the genus Procloeon Bengtsson 1915; it shares all characters of Procloeon s. l. and besides them, has peculiar autapomorphies in mouthparts structure. Diagnoses of Cloeon/fg1 (or the tribe Cloeonini sensu Kluge 2016), Procloeon/g1 (or the genus Procloeon sensu Kluge 2016) and Securiops are given. Larvae of the South African species Procloeon (Securiops) falcatum (Crass 1947) comb. n. are described for the first time. Based on reared specimens from Zambia, larvae of Procloeon (Securiops) macafertiorum Lugo-Ortiz (in Lugo-Ortiz & McCafferty) 1996 are redescribed; subimagines, imagines and eggs of this species are described for the first time. New larval characters of Procloeon (Securiops) mutadens (Jacobus et al. 2006) comb. n. are reported based on a larva from Gambia. Based on reared specimens from Thailand, larvae of Procloeon (Securiops) primasia (Kaltenbach et al. 2023) comb. n. are redescribed; subimagines, imagines and well-developed eggs of this species are described for the first time. Genitalia of Cheleocloeon excisum (Barnard 1932) are figured for the first time.